2022
DOI: 10.1186/s12887-022-03506-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and determinants of newbornsnot receiving postnatal check-up withintwodays after birth in Ethiopia: a spatial and multilevel analysis of EDHS 2016

Abstract: Background Accessibility and utilization of postnatal newborn check-ups within 2 days after delivery are critical for a child’s survival, growth, and development. However, the service delivery is not yet improved and fluctuates across the geographical locations in Ethiopia. Therefore, this study aimed to assess the spatial distribution and determinants of newborns not received postnatal check-ups within 2 days after birth in Ethiopia. Methods A sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
5
5
0
Order By: Relevance
“…The study found that 72.55% of women give birth at home, which is consistent with previous studies from Southeast Ethiopia (73.6%) [ 31 ], EDHS 2016 report (73.3%) [ 32 ], and Gozamin District in Amhara region (75.3%) [ 33 ], but higher than studies from Afar, Ethiopia (65%), South Ethiopia (62.2%), and Arba Minch town Ethiopia (33.2%) [ 34 36 ], Zala woreda, Southern Ethiopia (67.6%) [ 13 ], Anlemo District, Hadiya Zone (49.3%) [ 1 ], and Wolaita and Dawro Zone (62%) [ 1 , 14 , 37 , 38 ]; in contrast it is lower than a study conducted in Arbaminch Zuria District (79.4%) [ 39 ], zone 3 of Afar region (83.3%) [ 40 ]. In terms of PNC following deliveries, around 91.45% of women did not have a PNC after giving birth; this finding is consistent with studies conducted in Ethiopia [ 41 ], but slightly higher and lower than studies conducted in the same country [ 42 , 43 ] respectively. This variation could be attributable to the study area, setting difference, cultural attitude towards health facility delivery, infrastructure difference (access to the health facility, roads, and distance to the health facility).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The study found that 72.55% of women give birth at home, which is consistent with previous studies from Southeast Ethiopia (73.6%) [ 31 ], EDHS 2016 report (73.3%) [ 32 ], and Gozamin District in Amhara region (75.3%) [ 33 ], but higher than studies from Afar, Ethiopia (65%), South Ethiopia (62.2%), and Arba Minch town Ethiopia (33.2%) [ 34 36 ], Zala woreda, Southern Ethiopia (67.6%) [ 13 ], Anlemo District, Hadiya Zone (49.3%) [ 1 ], and Wolaita and Dawro Zone (62%) [ 1 , 14 , 37 , 38 ]; in contrast it is lower than a study conducted in Arbaminch Zuria District (79.4%) [ 39 ], zone 3 of Afar region (83.3%) [ 40 ]. In terms of PNC following deliveries, around 91.45% of women did not have a PNC after giving birth; this finding is consistent with studies conducted in Ethiopia [ 41 ], but slightly higher and lower than studies conducted in the same country [ 42 , 43 ] respectively. This variation could be attributable to the study area, setting difference, cultural attitude towards health facility delivery, infrastructure difference (access to the health facility, roads, and distance to the health facility).…”
Section: Resultssupporting
confidence: 87%
“…Postnatal care research in developing countries is scarce in comparison to antenatal care and skilled attendance at birth [ 12 ]. Few recent findings indicated that numerous characteristics, including Marital status, knowledge of the mothers on PNC service, place of residence, media exposure, place of delivery, residency, ANC follow-up, and administrative region, have been considered as determinants of postnatal care service utilization [ 17 , 18 ]. However, several studies have mainly neglected the potential impacts of geographical factors [ 19 , 20 ], and parallel effects (bivariate effects) of the place of delivery on the evaluation of PNC [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, children delivered at health institutions have higher odds of early newborn care than home-delivered mothers. This is supported by a study in Uganda 31 , and Ethiopia 14 . Moreover, in this study mothers who delivered through cesarean section were more likely to have immediate newborn postnatal care than other delivery modes.…”
Section: Discussionsupporting
confidence: 59%
“…This is also in line with another study in Ethiopia 44 . This could be because mothers who gave birth at home are culturally restricted from moving out of their homes for a certain period, which reduces postnatal care utilisation 14 . Therefore, if the care is not given home to home, they might miss their visit 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation